SOCIOECONOMIC STATUS AND MISSED CLINICAL APPOINTMENTS IN AGE-RELATED MACULAR DEGENERATION. (11th November 2018) - Dougherty, B; Cooley, S; Deffler, R; Davidorf, F
Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness in older adults. We have previously found that socioeconomic status (SES), as represented by educational achievement, is inversely related to visual acuity in people being treated for AMD. The purpose of this study was to evaluate possible mechanisms for this relationship in patients with AMD, specifically attendance at scheduled clinical appointments with a retina specialist, access to transportation, and having had a low vision rehabilitation examination. Methods: Visual acuity with habitual correction was measured via ETDRS chart with letter-by-letter scoring. SES was represented as highest level of education. Visual function and social support scales were administered and scored using Rasch analysis. ANOVA and Fisher's Exact Tests were used to examine the relationships among SES, VA, and clinical and transportation variables. Results: 42 people with AMD (37% female, mean±SD age of 77 ± 10 years) were recruited from The Ohio State University retina service. 54% of subjects missed at least one appointment that was not rescheduled within a month. Missed clinical appointments were more common among low SES groups (p=0.42). Having missed an appointment was associated with older age (p=0.032) and worse self-reported visual function (p=0.029). Only 7% of subjects reported difficulty finding transportation to appointments. Conclusion: Lower SES was related to an increased likelihood of missed appointments in people with AMD, as well as poorer visual functioning. Attendance at clinical appointments may be a factor in explaining the relationship between lower SES and poor vision in people with age-related macular degeneration.